Fibromyalgia syndrome and the immune system: a review with comparative perspectives on chronic immune-related syndromes including CFS/ME and IBS - Marta Nizzero; Vittorio Schweiger; Alvise Martini; Leonardo Gottin; Giustino Varrassi; Giovanna Del Balzo; Erica Secchettin; Luca Polati; Stefano Coaccioli; Enrico Polati (Exploration of Immunology)
Fibromyalgia syndrome (FMS) is a chronic condition characterized by widespread musculoskeletal pain, fatigue, cognitive impairments, and sleep disturbances. Although traditionally considered psychogenic, recent research supports a multifactorial etiology involving central nervous system (CNS) dysregulation and significant immune involvement. This narrative review synthesizes current evidence regarding the role of immune mechanisms in FMS, with comparative insights into chronic fatigue syndrome/myalgic encephalomyelitis (CFS/ME) and irritable bowel syndrome (IBS)—previously grouped under functional somatic syndromes (FSS). In FMS, immune dysregulation is evidenced by elevated levels of pro-inflammatory cytokines (e.g., IL-6, IL-8, TNF-α) and decreased anti-inflammatory mediators such as IL-10, contributing to symptomatology including pain amplification and fatigue. Neuroinflammation, as indicated by microglial activation in pain-processing CNS regions, further supports the role of immune signaling in central sensitization. Other contributing factors include oxidative stress, mitochondrial dysfunction, and immune cell alterations, particularly involving regulatory T cells and natural killer (NK) cells. Compared to FMS, CFS/ME exhibits greater systemic immune activation and more severe mitochondrial impairment, correlating with profound fatigue and cognitive decline. IBS, on the other hand, shows immune activation localized to the gastrointestinal tract, emphasizing the gut-brain axis. These findings highlight both shared and syndrome-specific immune features. To better reflect their systemic and immunological complexity, this review refers to these conditions collectively as chronic multisystem immune-related disorders (CMIRDs). The evidence supports the development of biomarker-based diagnostics and personalized immunomodulatory therapies. A multidisciplinary approach that integrates immunology and neurology is essential to improve outcomes for patients with FMS and related disorders.